Treść propozycjonalna i cele illokucyjne ekspresywnych aktów interiekcyjnych - Błaszczyk, Michał (Przegląd Rusycystyczny, 2007)
PROPOSITIONAL CONTENT AND ILLOCUTIONARY POINTS OF INTERJECTIVE EXPRESSIVES S u m m a r y The aim of the present article is to prove that, fi rst, emotive interjections do have propo-sitional content and, second, the acts of using exclamations have some unique illocutionary points. The fact that interjections have propositional content manifests itself in the process of forming innovative interjective utterances during which speakers create unconventional exclamations by way of modifying the semantic, syntactic and phonemic elements of con-ventional ones. As for the illocutionary points of interjective expressives (i.e. expressives performed by way of using emotive interjections), among the latter there are acts of attacking, begging, praising and complaining directed at no one (or nothing) in particular. ПРОПОЗИЦИОНАЛЬНОЕ СОДЕРЖАНИЕ И ИЛЛОКУТИВНЫЕ ЦЕЛИ МЕЖДОМЕТНЫХ ЭКСПРЕССИВ Р е з ю м е Цель настоящей статьи состоит в доказании верности гипотезы о том, что эмоци-ональные междометия являются высказываниями, имеющими пропозициональное содержание, и что применение восклицаний данной группы служит иллокутивным целям не встречаемым ни в каких других актах. Факт, что у междометий есть про-позициональное содержание, обнаруживается в процессе образования инноваци-онных эмоциональных междометий, в рамках которого отправители производят неконвенциональные высказывания, модифицируя семантические, синтаксические и фонологические составные конвенционализмов. Что же касается иллокутивных целей междометных экспрессив (т.е. экспрессив осуществляемых путем применения эмоциональных междометий), среди последних есть акты нападения и сетования ни на кого (что), мольбы ни к кому и восхищения ничем конкретным.